The Role Of Financial Behavior In Mediating The Effect Of Financial Attitude And Financial Knowledge On Investment Decision-Making At The Investment Gallery Of Universitas Bhayangkara Jakarta Raya - Anugerah Nurul Lucky; Muhammad Richo Rianto; Ari Sulistyowati (Draf Solusi Indonesia, 2026)
This study aims to determine the factors that influenceinvestment decisions among Generation Z, particularlystudents who are members of the Investment Gallery atBhayangkara University Jakarta Raya. The phenomenon ofincreasing investment interest among young generationsserves as an important basis for identifying the maindeterminants in making investment decisions. The variablesanalyzed in this study are financial attitude (X1), financialknowledge (X2), and financial behavior(Z) on investment decision (Y). The research method used isquantitative with a survey approach through the distributionof questionnaires to respondents who are active students ofthe Investment Gallery.